2016
DOI: 10.1038/ncomms11460
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of ASIC3 in sensory mechanotransduction in proprioceptors

Abstract: Acid-sensing ion channel 3 (ASIC3) is involved in acid nociception, but its possible role in neurosensory mechanotransduction is disputed. We report here the generation of Asic3-knockout/eGFPf-knockin mice and subsequent characterization of heterogeneous expression of ASIC3 in the dorsal root ganglion (DRG). ASIC3 is expressed in parvalbumin (Pv+) proprioceptor axons innervating muscle spindles. We further generate a floxed allele of Asic3 (Asic3f/f) and probe the role of ASIC3 in mechanotransduction in neurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
134
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(152 citation statements)
references
References 61 publications
11
134
0
Order By: Relevance
“…Over the years, additional ion channels were implicated in mechanosensory transduction, including MEC/DEG/ASICS and TRPs in lower organisms, as well as in mammals (Chalfie, 2009;Christensen and Corey, 2007;Lin et al, 2016;Walker et al, 2000;Yan et al, 2013). However, so far no clear evidence was provided demonstrating their intrinsic mechanosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, additional ion channels were implicated in mechanosensory transduction, including MEC/DEG/ASICS and TRPs in lower organisms, as well as in mammals (Chalfie, 2009;Christensen and Corey, 2007;Lin et al, 2016;Walker et al, 2000;Yan et al, 2013). However, so far no clear evidence was provided demonstrating their intrinsic mechanosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of ASIC3 to nociceptive mechanotransduction under the physiological condition is a matter of debate (Cheng et al, ; Deval & Lingueglia, ; Lingueglia, ), whereas ASIC3 is reported to be involved in proprioceptive mechanotransduction (Lin et al, ). In the present study, a selective blocker of ASIC3 administered to the naïve muscle via intramuscular injection did not alter the mechanical withdrawal threshold, indicating that ASIC3 played no role in the normal mechanical pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The beam walking test was conducted using a previously described method (Lin et al, ), with slight modifications. Briefly, mice were placed at a fixed point on a 0.5 cm wide ruler attached to a goal box (non‐transparent, 20 × 10 × 20 cm 3 ).…”
Section: Methodsmentioning
confidence: 99%